A scoping review on population-centered indicators for cancer care continuum - Rajaguru, Vasuki; Jang, Jieun; Kwon, Jeoung A.; Kim, Jae Hyun; Shin, Jaeyong; Chun, Mison (Frontiers in Public Health, 2022)
Purpose: To develop prioritized cancer indicators and measure the population-based monitoring of the entire cancer-care life cycle, to guide the improvement of care delivery systems. Methods: Scoping review was performed, based on the Joanna Briggs Institute’s methodology. Electronic databases were searched in: Cochrane Library, EMBASE, Ovid Medline, PubMed, RISS, KISS, and Korea Med. The searches were limited to articles published in English between 2010 and 2020. No restrictions were applied regarding the publication status or country of origin, and all study designs were included. Grey literature was included to increase the sensitivity of the search, additional guidelines identified, experts contacted, and applicable websites perused. The process and selected indicators were analyzed based on their frequency distribution and percentage. Results: The literature search yielded 6,202 works. Additionally, national, and international cancer guidelines were obtained from official database reports. Thirty-five articles and twenty reports regarding cancer indicators were finally selected for data synthesis. Based on them, 254 core sets of cancer indicators were identified. The selected indicators were classified into six domains based on the continuum of cancer care and survivor’s life cycle: primary prevention (61, 24.0%), secondary prevention (46, 18.1%), treatment (85, 33.5%), quality of care (33, 13.0%), survivor management (33, 13.0%), and end-of-life care (14, 5.5%). Conclusions: There is growing interest in developing specific areas of cancer care. Cancer indicators can help organizations, care providers, and patients strive for optimal care outcomes. The identified indicators could guide future innovations by identifying weaknesses in cancer prevention and management.